What restraints are there on female education in high mountainous rural areas of Gilgit-Baltistan, Pakistan. Issue 8 (17th November 2021) - Ali, Iftikhar; Khan, Mohsin; Alam, Arif
ABSTRACT: Women's participation in higher education is mainly attributed to varying socioeconomic and cultural practices. By employing a survey and focus group discussion, we ascertained the social and cultural determinants and the impact on female higher education in the high mountainous rural areas of Gilgit-Baltistan province of Pakistan. Through analysing responses from 160 participants, we found that low levels of parental education, gender biases, safety concerns, and early-age marriages are some of the dominating sociocultural constraints on female higher education. Likewise, demographic and economic factors including the parents' age, occupation, and level of income also influence the participation of females in higher education. It is imperative to engage various stakeholders such as local community, parents, and religious leaders to address parental concerns and overcome the sociocultural restraints on female higher education, and for developmental practitioners to ensure access and opportunities for females in Gilgit-Baltistan.